Review on Li-Ion Battery with Battery Management System in Electrical Vehicle - Ramkumar, M. Siva; Reddy, C. Subba Rami; Ramakrishnan, Agenya; Raja, K.; Pushpa, S.; Jose, S.; Jayakumar, Mani (Advances in materials science and engineering, 2022)
In this paper, functions of BMS in elections vehicles are explained. The BMS consists of number of electronics components for monitoring and controlling the functions of batteries in electrical vehicles (EVs). Nowadays, the EV has more concentrations because it has number of merits like compact in size, does not require fossil fuel so it is environment friendly, and cost-saving. The main components in EV are batteries because batteries decide the performance and efficiency of EV. So, we should give more importance to batteries. Battery is controlled and monitored with the help of BMS. The BMS protects the battery and increases life time and efficiency due to charging discharging process.